2018
DOI: 10.1146/annurev-environ-102017-025855
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Climate Change

Abstract: Understanding the cultural dimensions of climate change requires understanding its religious aspects. Insofar as climate change is entangled with humans, it is also entangled with all the ways in which religion attends human ways of being. Scholarship on the connections between religion and climate change includes social science research into how religious identity figures in attitudes toward climate change, confessional and constructive engagements of religious thought with climate change from various communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 134 publications
2
88
0
3
Order By: Relevance
“…They state that their "common interpretations of core evangelical beliefs led primarily to climate scepticism" (Carr et al 2012, p. 278). Jenkins et al (2018) state, however, that other scholarship has concluded that religious beliefs are only one determinant factor in how an individual perceives climate change. They suggest that that which determines an individual's opinion on climate change is more dependent upon a network of relations regarding education, political beliefs, and geographic location.…”
Section: The Politics Of the Sacredmentioning
confidence: 76%
See 2 more Smart Citations
“…They state that their "common interpretations of core evangelical beliefs led primarily to climate scepticism" (Carr et al 2012, p. 278). Jenkins et al (2018) state, however, that other scholarship has concluded that religious beliefs are only one determinant factor in how an individual perceives climate change. They suggest that that which determines an individual's opinion on climate change is more dependent upon a network of relations regarding education, political beliefs, and geographic location.…”
Section: The Politics Of the Sacredmentioning
confidence: 76%
“…Debate over climate change is caught up in the spheres of the political and the religious. Religious bodies, especially multifaith organisations, such as ARRCC, have long been advocating for environmental rights (Halafoff 2013;Jenkins et al 2018). However, there are also many who occupy a position of climate change denialism.…”
Section: The Politics Of the Sacredmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research from primarily environmental sociology and psychology has shown that religious orientations play an important role in sustainability issues (for overviews cf. Tomalin et al 2019;Jenkins et al 2018;Basedau et al 2017;Ronan 2017;Sachdeva 2016;Haluza-DeLay 2014;Tucker 2006), although the connections are by no means clear. Whether religious orientations positively or negatively affect the formation of a sustainable environmental orientation depends on many personal and contextual factors, and not least, on the respective religious orientation itself (Baugh 2019;Ives and Kidwell 2019;Basedau et al 2017;Pater and Dankelman 2009;Sherkat and Ellison 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As one might expect, Francis speaks of spiritual and scientific and technological realities and puts these at the service of ecological restoration and social progress, including a section explicitly dedicated to “religions in dialogue with science” (Francis 2015, 145–8). Meanwhile, there is evidence that the encyclical had both positive and negative impacts on environmental thinking (see Jenkins, Berry, and Krieder 2018, 9.4)!…”
Section: A Hydra‐logical Approachmentioning
confidence: 99%